Pengaruh Kedisiplinan Dan Fasilitas Kerja Terhadap Kinerja Karyawan Di CV. Pantai Romantis Group Serdang Bedagai - Aisarah Aisarah; Dian Purnama Sari; Winda Wardhani (Universitas Veteran Bangun Nusantara, 2023)
This study aims to determine whether discipline and work facilities either partially or simultaneously have a significant influence on the performance of employees at CV. Serdang Bedagai Group's Romantic Beach and how much influence it has. The method used in this study is a quantitative method with several tests, namely reliability analysis, classical assumption deviation test and linear regression. Based on the results of the primary data regression processed using SPSS 20, the multiple linear regression equation is obtained as follows: Y = 6.666 + 0.185 X1 + 0.636X2 + e. Partially, the discipline variable (X1) has no significant effect on employee performance, as evidenced by the t count < t table (1.993 < 1.994). The work facility variable (X¬2) has a significant influence on employee performance, as evidenced by the t count > t table (6.429 > 1.994). Simultaneously, the discipline variables (X1) and work facilities (X2) have a significant influence on employee performance. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (39.615 > 3.13). Discipline variables (X1) and work facilities (X2) are able to contribute to the influence of the performance variable by 53.1% while the remaining 46.9% is influenced by other variables not examined in this study. From the conclusions above, the authors provide suggestions seeing that there is still a lack of high employee discipline values, this should be a concern of management so that employees can improve discipline so that CV increases. The Serdang Bedagai Romantic Group Beach is more visible. Employee work facilities and tourist facilities that are already quite good are expected to be improved again, so that employee performance and visitor satisfaction will increase. It is hoped that there will be in-depth research in the future by other researchers regarding the variables of discipline and work facilities on performance.